Early introduction of science and technology through optimizing the use of Science Props media for MI Muhammadiyah Wonorejo students - Mohtar Yunianto; Suparmi Suparmi; Cari Cari; Fuad Anwar; Suharyana Suharyana; Darmanto Darmanto (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Learning science and technology to children so far by telling stories so that children are easily bored, and as a result, children lack understanding of science and technology learning. Efforts in introducing science and technology to early childhood have been made to minimize this incident. The activity is in the form of training in using electrical and magnetic props for MI Muhammadiyah Wonorejo students. The activity begins with a pretest to determine students' initial ability, followed by introducing the concept of theory and practice of props in groups, electrical material related to series and parallel circuits for magnetism related to static magnets and dynamic magnets. The result is that there is more interest from students to learn, and there is an increase in student understanding of magnetic electricity material and can use of teaching aids.